The Effects of Entrepreneurial Orientation on Organizational Performance - Mateusz CODOGNI (Communications of International Proceedings, 2021)
Entrepreneurship is considered one of the main forces for the development of organizations, and entrepreneurial orientation is a driving force behind entrepreneurial activities. The aim of this paper is to test the effect of entrepreneurial orientation on the growth rate of companies. To that end, a study has been carried out on a sample of 58 furniture manufacturing companies from Małopolska region in Poland. The main findings are that entrepreneurial orientation does in fact affect the growth rate of companies and that entrepreneurial orientation as a single construct consisting of three dimensions is a better predictor of company growth than any of its dimensions individually, which points to the conclusion that the concurrent exhibition of innovativeness, risktaking and proactiveness creates a synergistic effect that translates to company growth.
Keywords: SME; Entrepreneurial Orientation (EO); Organizational Performance; Organizational Growth